Estudio sobre el desarrollo del sabalito Pseudocurimata gilberti Fernández-Yepes 1948 y descripción preliminar del desarrollo de Cheirodon interruptus interruptus (Jenyns, 1842) - Freyre, Lauce Rubén (1971)
An indication of the ecological placing of Psedocurimata gilberti in the environment studied, accompanies a description of the hypophysation methods employed, the morphology of the egg, the system of artificial fertilization and the main stages of the evolution of the egg and larval development, computed by time and degrees per hour. Special consideration has been takenn of certain structures which notwithstanding the opinion of earlier writers we interpret as being larval neuromasts and state summarily the possibility of their onto-phylogenetic relationships. Two last observations rnade coincide with the appearing of the seales. We describe the morphology of the egg of Cheirodon interruptus interruptus, the principal stages of evolution of the egg and of the development of the larva up to the 14th day of its growth, together with observations on the trophic behaviour during the last stage studied.